Academic Predictors of Performance in the Board Licensure Examination for Psychometricians - Jose J. Pangngay; Chester Alan R. Merza; Maria Lourdes R. Almojuela (Philippine Social Science Journal, 2023)
In relation to the adherence of Higher Education Institutions (HEIs) offering undergraduate psychology programs to excellent standards of education as translated in the Board Licensure Examination for Psychometricians (BLEP), this study aimed to analyze the predictors of BLEP performance as inputs to curriculum and instruction quality assurance. This study employed a descriptive-quantitative design and collected data using an online survey and data mining. Results from one private-sectarian HEI show that general academic performance – specifically in Theories of Personality, Abnormal Psychology, Industrial Psychology, and Dynamic Psychology courses – were significant predictors of BLEP performance, suggesting that better undergraduate academic performance leads to better BLEP performance. These results highlight the need for enhancing the curriculum and instruction in response to the demands of various regulatory and quality assurance bodies in ensuring that the mandate of HEIs to produce high-quality professionals is achieved through a curriculum-based course audit for review classes and intensified instruction.